Bleaching and degradation of textile dyes by nonthermal plasma process at atmospheric pressure - Abdelmalek, Fatiha; Ghezzar, Mouffok R; Belhadj, Mohamed; Addou, Ahmed; Brisset, Jean-Louis (Industrial & engineering chemistry research, 2006)
The degradation of aqueous solutions of various dyes (e.g., Orange I, Crystal Violet, and Eriochrome Black T) used for the textile industry was performed by means of a special nonthermal quenched plasma technique (i.e., the gliding arc technique, which results from an electric discharge at atmospheric pressure and ambient temperature). The gaseous species formed in the discharge, and especially the OH radicals, induce strong oxidizing effects in the target solution, so that bleaching of the solution and degradation of the solute result, as evidenced by absorbance and chemical oxygen demand (COD) measurements. The two processes were considered as matching reactions, and overall kinetic data were derived when possible. A tentative mechanism based on literature data is also presented.